2012
DOI: 10.4274/jcrpe.560
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Defects of the Thyroid Gland: Relationship with Advanced Maternal Age

Abstract: Objective: Developmental defects of the thyroid gland are the most frequent causes of permanent congenital hypothyroidism. This study aimed to investigate the epidemiological features of patients with thyroid dysgenesis (TD).Methods: Medical records of 234 patients with TD followed between the years 2008 and 2010 were evaluated retrospectively. Diagnosis was made by ultrasonography.Results: Of 234 patients, 120 (51.3%) were male and 114 (48.7%) were female. Male to female ratio was 1.08 and there were no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
3
17
1
Order By: Relevance
“…Reported risk factors for transient CH were as follows: iodine deficiency or excess, prematurity, old maternal age, male gender, retinopathy of prematurity, twin pregnancy, maternal autoimmune thyroid disease, intrauterine growth retardation, and cesarean delivery (19,24,26,33,51,56,63). Reported risk factors for permanent CH with dysgenesis of the thyroid gland were as follows: female gender, familial history of CH, birth in geographical areas with a high rate of the disease, old maternal age, ethnicity (Caucasians) but not seasonality (5,15,42,50,56,61).…”
Section: Resultsmentioning
confidence: 99%
“…Reported risk factors for transient CH were as follows: iodine deficiency or excess, prematurity, old maternal age, male gender, retinopathy of prematurity, twin pregnancy, maternal autoimmune thyroid disease, intrauterine growth retardation, and cesarean delivery (19,24,26,33,51,56,63). Reported risk factors for permanent CH with dysgenesis of the thyroid gland were as follows: female gender, familial history of CH, birth in geographical areas with a high rate of the disease, old maternal age, ethnicity (Caucasians) but not seasonality (5,15,42,50,56,61).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, results of the current study and our past work [Hoshiko et al, ] suggest stronger associations with neonatal T4 levels in certain analyses, potentially indicating subgroup‐specific susceptibilities or modifiers of the primary relationship. Thyroid defects have been previously associated with advanced maternal age [Kirmizibekmez et al, ], which is also an established risk factor for ASD [Shelton, Tancredi, & Hertz‐Picciotto, ]. Low birth weight, too, has been associated with both TH and ASD, and results of one small study suggested higher risk of ASD in low birth weight infants with transient hypothyroxinemia [Korzeniewski et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Another study from Turkey found an increased incidence of thyroid hypoplasia but attributed this to noninclusion of thyroid scintigraphy. [ 7 ] Indian data obtained during 1990s suggested that agenesis and/or hypoplasia was the predominant form of TD in children belonging to iodine deficient regions, and postulated that iodine deficiency may lead to TD. [ 8 ] Iodine deficiency contributing to TD seems unlikely, as our study population belongs to a nonendemic area.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 5 ] Higher prevalence is attributed to genetic factors resulting from frequent parental consanguinity. [ 4 6 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation